A Rare Case of Cyclotorsion Due to Medial Rectus Displacement Following Orbital Trauma. Issue 1 (15th April 2021) - Green, Elspeth; Harwood, Hannah; Bansal, Shveta
We describe a rare case of cyclotorsion likely secondary to medial rectus and inferior rectus pathology in a patient with orbital trauma. Sequential orthoptic measurements including Hess charts are presented alongside relevant sections of the orbital CT scans over the course of the patient's treatment. Following the insertion of a plate to repair an orbital floor fracture, the patient developed cyclotorsion. A combined approach of sequential orthoptic assessment and imaging revealed the likely underlying mechanism. Inferior rectus mechanical restriction combined with displacement of the medial rectus pulley appear to be the likely culprits. Once the orbital plate was exchanged for a smaller sized plate the patient's symptoms and clinical features resolved. Although orbital plate malpositioning is not an uncommon event, medial rectus deviation as a cause of cyclotorsion has not previously been described. We discuss the alternative differentials for patients with similar orthoptic findings and how they were excluded.